New picolinate-functionalized titanium-oxide clusters: syntheses, structures and photocatalytic H2 evolution. Issue 40 (23rd September 2022) - Gao, Chang; Wang, Dexin; Liu, Yanshu; Zhang, Guanyun; Liu, Caiyun; Said, Amir; Niu, Huihui; Wang, Guo; Tung, Chen-Ho; Wang, Yifeng
Abstract : Two new TOCs functionalized with 2-picolinate were synthesized. Their photocatalytic H2 evolution activities were very different. In situ formation of PtNPs supra-nanoparticle assemblies was observed, which could be the photocatalytic active species. Abstract : Two nanosized titanium-oxide clusters (TOCs), Ti12 (μ2 -O)14 (μ3 -O)4 PA16 (1 ; PA = 2-picolinate) and Ti12 (μ2 -O)18 PA18 (2 ) were synthesized by using 2-picolinic acid and Ti(O i Pr)4 in one-pot reactions. Their structures were determined using single-crystal X-ray diffractometry. Although both have the same core composition of Ti12 O18, 1 exhibited superior H2 evolution activity of up to 180 μmol h −1 g −1, which is nearly eight times faster than 2 . Mechanism studies revealed that 1 could induce the assembly of 2.3 nm PtNPs into 10–30 nm supra-nanoparticle structures, which contributed to the increased H2 evolution rate.